2015
DOI: 10.5935/0101-2800.20150014
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia in Chronic Kidney Disease

Abstract: Sarcopenia is a chronic condition associated with physiological aging process and is defined by the reduction of the mass, muscle strength and function. In Chronic Kidney Disease (CKD), sarcopenia is prevalent and is associated with increased morbidity and mortality and the occurrence of cardiovascular complications. By analyzing sarcopenia in patients with renal insufficiency, complex mechanisms that contribute to loss of muscle mass are highlighted, such as activation of mediators that stimulate the ubiquiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 59 publications
2
44
0
13
Order By: Relevance
“…Osteomalacia is a well-known cause of proximal myopathy predominantly with atrophy of type II muscle fibers [97]. Sarcopenia is highly prevalent among CKD patients and is associated with increased morbidity and mortality [98,99]. Nevertheless, the role of lower 25(OH)-VD levels in the pathogenesis of CKD-related sarcopenia remains unclear.…”
Section: Vd and Ckd: Human Studiesmentioning
confidence: 99%
“…Osteomalacia is a well-known cause of proximal myopathy predominantly with atrophy of type II muscle fibers [97]. Sarcopenia is highly prevalent among CKD patients and is associated with increased morbidity and mortality [98,99]. Nevertheless, the role of lower 25(OH)-VD levels in the pathogenesis of CKD-related sarcopenia remains unclear.…”
Section: Vd and Ckd: Human Studiesmentioning
confidence: 99%
“…The aetiology of uremic myopathy is multifactorial ( Table  2), including physical inactivity, reduced protein intake, vitamin D deficiency, hyperparathyroidism, metabolic acidosis, electrolyte disorder, low serum levels of testosterone, resistance to growth hormone and insulin, accumulation of uremic toxins, and carnitine deficiency, which can lead to mitochondrial dysfunction 105, 106. Observational studies have shown an inverse correlation between muscle mass and blood levels of IL‐6 and C reactive protein in CKD patients,12, 107, 108 postulating inflammation as an additional cause of muscle wasting in this population 109, 110, 111.…”
Section: Bone and Musculoskeletal Abnormalities In Chronic Kidney Dismentioning
confidence: 99%
“…A high prevalence of sarcopenia has been reported in developed and developing countries, and this disorder affects both healthy individuals and individuals with chronic diseases, including hypertension, diabetes, and chronic kidney disease (CKD) [79]. …”
Section: Introductionmentioning
confidence: 99%